STRATEGI KEBIJAKAN PENGURANGAN RISIKO BANJIR DI KABUPATEN GROBOGAN: STRATEGI KEBIJAKAN PENGURANGAN RISIKO BANJIR DI KABUPATEN GROBOGAN - Rahman, Abdur (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2025)
Flood disasters have become one of the most critical environmental issues in Grobogan Regency over the past two years. At least three major floods occurred in February and March 2024, and again in January 2025, inundating 98 villages across 14 subdistricts and breaching 28 river embankment points. These floods were triggered by extreme rainfall, inadequate flood control infrastructure, and uncontrolled land conversion from forest to agricultural areas in the upstream catchment zones. This policy paper aims to identify the main drivers of flooding and formulate short-, medium-, and long-term strategies for flood risk reduction in Grobogan Regency.The study employed a descriptive–qualitative approach using literature review, interviews with officials from the Regional Disaster Management Agency (BPBD) and the Regional Development Planning Agency (Bappeda), and direct field observations. The analysis applied the USG (Urgency–Seriousness–Growth) model to determine priority issues and the SWOT (Strengths–Weaknesses–Opportunities–Threats) framework to evaluate strategic options for policy intervention. The findings reveal that flood mitigation efforts should focus on strengthening water resource infrastructure, conducting regular river normalization, and enforcing stricter land-use control. Adaptive strategies such as agroforestry systems, upstream reforestation, and sustainable land management are essential to enhance climate resilience. Through cross-sectoral collaboration and ecosystem-based governance, Grobogan Regency can progress toward sustainable flood resilience.